Resuscitation of anammox bacteria after >10,000 years of dormancy - Zhu, G.; Wang, S.; Wang, C.; Zhou, L.; Zhao, S.; Li, Y.; Li, F.; Jetten, M.; Lu, Y.; Schwark, Lorenz (2018)
Water is essential for life on Earth, and an important medium for microbial energy and metabolism. Dormancy is a state of low metabolic activity upon unfavorable conditions. Many microorganisms can switch to a metabolically inactive state after water shortage, and recover once the environmental conditions become favorable again. Here, we resuscitated dormant anammox bacteria from dry terrestrial ecosystems after a resting period of >10 ka by addition of water without any other substrates. Isotopic-tracer analysis showed that water induced nitrate reduction yielding sufficient nitrite as substrate and energy for activating anammox bacteria. Subsequently, dissimilatory nitrate reduction to ammonium (DNRA) provided the substrate ammonium for anammox bacteria. The ammonium and nitrite formed were used to produce dinitrogen gas. High throughput sequencing and network analysis identified Brocadia as the dominant anammox species and a Jettenia species seemed to connect the other community members. Under global climate change, increasing precipitation and soil moisture may revive dormant anammox bacteria in arid soils and thereby impact global nitrogen and carbon cycles.